2022
DOI: 10.3390/bios12030146
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Dictionary Selection in Compressive Sensing for ECG Signals Compression and Classification

Abstract: The paper proposes a comparative analysis of the projection matrices and dictionaries used for compressive sensing (CS) of electrocardiographic signals (ECG), highlighting the compromises between the complexity of preprocessing and the accuracy of reconstruction. Starting from the basic notions of CS theory, this paper proposes the construction of dictionaries (constructed directly by cardiac patterns with R-waves, centered or not-centered) specific to the application and the results of their testing. Several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…On the other hand, sample recordings in ambient conditions and PD identification from continuous speech are pursued less in the literature. Moreover, none of the reviewed solutions attempts to solve this problem by using CNN [46][47][48]. As such, the speech assessment workflow proposed in this article is aimed towards the assessment of continuous speech acquired in a noisy environment.…”
Section: Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, sample recordings in ambient conditions and PD identification from continuous speech are pursued less in the literature. Moreover, none of the reviewed solutions attempts to solve this problem by using CNN [46][47][48]. As such, the speech assessment workflow proposed in this article is aimed towards the assessment of continuous speech acquired in a noisy environment.…”
Section: Present Studymentioning
confidence: 99%
“…Thus, the CNN improves the structure and performance of traditional artificial networks, and the architecture of these models is suitable for recognizing certain patterns, i.e., features from the structure of 2D images [47]. As a mode of use, the CNN achieved very good results in the analysis of medical images, image segmentation, or in the field of visual recognition [48].…”
Section: Cnn-based Spectrogram Classificationmentioning
confidence: 99%
“…Experiments have shown that if the ECG signal of the same patient for 24 hours needs to be detected in the ambulatory ECG. Then the PSCCS method can be chosen, and if the purpose is to identify and classify abnormalities in the ECG signal, the CPCS method with the presence of pre-processing as well as segmentation is more effective [ 45 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The paper proposed by Monica fira et al [228] discusses the study on dictionary selection for ECG signals in CS domain. This article proposes the construction of dictionaries which are directly constructed from R waves.…”
Section: Learning On Reconstructed Ecg Signalmentioning
confidence: 99%